Effects of deployment of electric vehicles on air quality in the urban area of Turin (Italy). (1st November 2021) - Rizza, Valeria; Torre, Marco; Tratzi, Patrizio; Fazzini, Paolo; Tomassetti, Laura; Cozza, Valentina; Naso, Francesco; Marcozzi, Dino; Petracchini, Francesco
Abstract: This study aims to evaluate and quantify the environmental, health, and economic benefits due to the penetration of electric vehicles in the fleet composition by replacing conventional vehicles in an urban area. This study has been performed for the city of Turin, where road transport represents one of the main primary emission sources. Air pollution data were evaluated by ADMS-Roads, the flow traffic data used for simulation come from a real-time monitoring. Instead, statistics on mortality and hospitalizations due to cardiovascular and respiratory diseases were collected from the regional health information system and the National Health Institute and implemented in the BenMap software to evaluate the health and economic impacts. In both cases, two scenarios to evaluate the annual benefits of reducing PM10, PM2.5 and NO2 were used: reduction to the levels gained by the assumptions of 2025 and 2030 Scenario and the PM10, PM2.5 and NO2 concentrations were considered for evaluating short-term and long-term effects. The analysis performed doesn't include background pollution levels, i.e. the concentrations percentage reductions are only related to the local contribution, therefore derived from the contribution only of traffic source. The results show that fleet electrification has a potential benefit for concentrations reduction in comparison to the base Scenario, especially related to NO2, less for PM10 and PM2.5 . Regarding 2025 Scenario (4 % (passenger car) and 5 % (light-duty vehicles) electric vehicles), reductions of 52 % of NO2, 35 % of PM10 and 49 % of PM2.5 are observed. Meanwhile, as regards 2030 Scenario reductions of 87 % of NO2, 36 % of PM10 and 50 % of PM2.5 are reached. Also, in terms of social costs a decrease of 47 % for the 2025 Scenario and 66 % for the 2030 Scenario in comparison to the base Scenario is arise. Highlights: A 5 % share of electric vehicles reduces NO2 concentrations by 52 %. Particulate matter is less impacted by the number of circulating electric vehicles. Social benefits due to lower pollutant concentrations are significant (reduction of 47 % and 66 % in terms of social costs). ADMS-Roads enhanced by real-time traffic data is a valid predictive tool.